Effect of Dimensional Aspectsservice Quality Reliability and Responsiveness on Go-Food Customer Satisfaction in Bandar Lampung - Aimar, Muhammad Pablo; Sari, Wenny Permata (PT FORMOSA CENDEKIA GLOBAL, 2024)
Reliability(reliability), the company's capability to provide appropriate services according to commitments and to carry out services based on agreed commitments within the specified time, if consumer satisfaction will increase it means they are served appropriately and vice versa, while responsiveness is the ability to provide solutions to customers and provide services appropriate services and the ability of company employees to provide services quickly and responsively (Tjiptono, 2019). The aim of this research is to understand whether reliability and responsiveness influence customer satisfaction. This research sample involved 100 respondents who live in Bandar Lampung and aged 17 years and over with the sample determination method, namelypurposive sampling. Multiple linear regression analysis is the statistical method applied in this research. Data was collected through a questionnaire and after processing the t test results were obtained: (1) Proving that reliability does not significantly influence customer satisfactionGofood in Bandar Lampung and (2) responsiveness significantly influences customer satisfactionGofood in Bandar Lampung (3) Based on the f test, it states that customer satisfaction is influenced simultaneously by the variables of reliability and responsiveness.